Pengaruh Konseling Kelompok Dengan Pendekatan Realita Terhadap Konsep Diri Remaja - Pratiwi, Astri (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of applying group counseling with a realityapproach to adolescent self-concept at the Muhammadiyah Orphanage in Magelang City.This study uses the One Group Pretest Posttest Design. The samples taken in this studywere 8 teenagers as the experimental group. The sampling approach used a purposivesampling approach because in accordance with the characteristics of the study, in thisstudy were adolescents who had negative self-concepts. The data analysis method used isPaired sample t-test parametric analysis with the help of IBM SPSS Statistics 24.0.The results showed that the reality approach group counseling had an effect on adolescent self-concept. This is evidenced by the results of the Parametric Statistics Paired sample t-test with a significance value probability (2-tailed) of 0.002 < 0.05. There is a difference in the average score of the self-concept questionnaire 19% from the pretest results of the self-concept questionnaire and the posttest results of the self-concept questionnaire. The results of this study can be concluded that the reality approach group counseling has aneffect on improving self-concept in adolescents.